Influence of exchange rate fluctuations and credit supply on dividend repatriation policy of U.S. multinational corporations - Muhammad Tahir; Haslindar Ibrahim; Abdul Hadi Zulkafli; Muhammad Mushtaq (Journal of Central Banking Theory and Practice, 2020)
This study aims to examine the effect of exchange rate fluctuations and credit supply on the dividend repatriation policy of foreign subsidiaries of U.S. multinational corporations (MNCs) around the world. The difference generalised method of moments (GMM) estimator was applied to estimate the dynamic dividend repatriation model. The results suggest that the appreciation of host-country currency against the USD leads to higher dividend repatriation by the foreign subsidiaries of U.S. MNCs. Moreover, results reveal that higher availability of private credit in the host country results in lower dividend repatriation by the U.S. MNCs' foreign subsidiaries.
Keywords: F23; F31; F34; G35; 330; Exchange rate fluctuations; Credit supply; Dividend repatriation policy; Generalised method of moments; Multinational corporations